Excitation functions for the Al-27(p, x)Na-22,Na-24 nuclear reactions up to 40 MeV - Khandaker, Mayeen Uddin; Kim, G.N.; Kim, K.; Lee, M.W.; Kim, K.S. (2011)
Excitation functions for the Al-nat(p, x)Na-22,Na-24 nuclear processes were measured in the proton energy range of 30-38 MeV using a stacked-foil activation technique combined with a high purity germanium (HPGe) gamma-ray spectrometry. Measured data were compared with the available literature data and theoretical calculation by the TALYS code. Validation of the measured data was done with the IAEA recommended ones.